2020
DOI: 10.1007/s00399-020-00721-8
|View full text |Cite
|
Sign up to set email alerts
|

Mahaim pathway potential revealed by high-resolution three-dimensional mapping

Abstract: Mapping and ablation of atriofascicular fibers can be highly challenging due to the complex and dynamic anatomy of the tricuspid valve annulus. This case highlights the utility of a multi-electrode catheter three-dimensional mapping approach to localize the Mahaim pathway along the tricuspid annulus in order to guide catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Steinfurt et al [4][5][6] revealed Mahaim fiber in the right ventricle by high-resolution 3D mapping using the CARTO 3 system (Biosense Webster, Irvine, CA, USA). [5] Nishimura et al tracked the course of Mahaim pathway using the Rhythmia TM system (Boston Scientific).…”
Section: Discussionmentioning
confidence: 99%
“…Steinfurt et al [4][5][6] revealed Mahaim fiber in the right ventricle by high-resolution 3D mapping using the CARTO 3 system (Biosense Webster, Irvine, CA, USA). [5] Nishimura et al tracked the course of Mahaim pathway using the Rhythmia TM system (Boston Scientific).…”
Section: Discussionmentioning
confidence: 99%